PENGUATAN DAN PENEGAKAN ATURAN-ATURAN ADAT (AWIG-AWIG) UNTUK MELINDUNGI EKSISTENSI TANAH ADAT DI LOMBOK - NI LUH ARININGSIH SARI (GANEC SWARA, 2024)
This research aims to explain the strengthening and enforcement of customary rules (awig-awig) to protect the existence of customary land in Lombok, and to determine the obstacles faced in efforts to enforce customary rules (awig-awig) to protect customary land in Lombok. That to strengthen and enforce customary rules / awig - awig is to put them in written form so that there is legal certainty, and future generations can continue to guide the awig - awig. The obstacles faced and the solutions are Concern for their own cultural traditions by the next generation is increasingly diminishing due to the enormous influence of globalization without any filter by traditional elders or families/parents for their children; It is very important for regional governments to revive cultural customs in every region that has indigenous communities by holding cultural festivals or similar activities so that the younger generation begins to understand, appreciate and love their own regional culture, they are proud to use products from their regional traditional crafts; Continuously sounding/broadcasting Lombok's cultural diversity at every opportunity, both nationally and internationally; Strengthen and uphold the awig-awig of indigenous communities through collaboration between indigenous communities, regional governments and academics